Experimental study of mixed additive of Ni(II) and piperazine on ammonia escape in CO2 capture using ammonia solution. (1st May 2016) - Ma, Shuangchen; Chen, Gongda; Zhu, Sijie; Wen, Jiaqi; Gao, Ran; Ma, Lan; Chai, Jin
Graphical abstract: Highlights: Compound additive was used to obtain high CO2 absorption efficiency and low NH3 escape. Both organic material and metal ion were applied as compound additive. Influences of additives on CO2 absorption and NH3 escape were investigated. Possible mechanism and products were analyzed by XRD and UV–visible spectrophotometer. Abstract: In order to obtain high CO2 absorption efficiency and low ammonia escape rate, mixed additives of piperazine and Ni(II) were used as absorbent in bubbling reactor. The effects of mixed additive on CO2 absorption efficiency and ammonia escape rate were investigated; the performances of mixed additive in removal process were compared with that of pure ammonia solution. The proposed mechanism was analyzed by XRD and UV–visible spectrophotometer. The mixed additive has well effect on CO2 absorption efficiency and ammonia escape reduction. The CO2 absorption efficiency was 72% when 2 wt% ammonia solution mixed with 0.025 mol/L piperazine and 0.05 mol/L Ni(II), higher than that achieved by 3 wt% ammonia solution without additive, and the amount of ammonia loss was nearly 1/3 compared with 3 wt% pure ammonia solution. This paper provided one feasible method which is beneficial to the balance between CO2 absorption and ammonia escape in CO2 capture process.